Mechanism and regulatory strategy study on promoting vascularized bone regeneration via intracellular zinc ion transport - Yitong Liu; Siyan Liu; Juan Du; Junji Xu; Jing Li; Lijia Guo; Yi Liu (Bioactive Materials)
Bone regeneration is a major clinical challenge. The main obstacles to bone injury repair are local blood flow disorders and hypoxic microenvironments. Mesenchymal stem cell (MSC) therapy has notable advantages in promoting bone-tissue regeneration. In this study, we established a mouse model of skull bone injury treated with bone marrow mesenchymal stem cells (BMSCs). We found that local BMSC transplantation stimulated vascularized bone regeneration and matrix metalloproteinase (MMP)10 was the major regulatory protein. Local hypoxic microenvironment-induced mitochondrial permeability increased, resulting in cytoplasmic Zn2+ accumulation, which is a key factor in activating the JAK1/STAT1/MMP-10 pathway. The cytoplasmic Zn2+ enrichment caused ZRT/IRT-like protein 6 (ZIP6) inhibition was the key initiating factor in this process. Based on these findings, we designed and engineered CD90@ZIF-8-ICG, with an outer membrane chimeric CD90 antibody containing indocyanine green (ICG), to achieve increased intracellular zinc ion content by targeted delivery of the particles into local MSCs, so that local MMP-10 production and angiogenesis are regulated at the early stage of healing. ICG provided BMSCs with continuous photothermal stimulation in response to the laser intervention, which successfully achieved stable improvement of bone-defect regeneration. This study innovatively describes the regulatory importance of intracellular zinc ion homeostasis and ZIP proteins in the function of transplanted MSCs, as well as the related efficiency strategy development, which elucidates MSC therapy treatment mechanisms and provides strategies for the design and development of stem-cell-based biomaterials.